Growth Rate of Acropora formosa Fragments that Transplanted on Artificial Substrate Made from Coral Rubble (Biodiversitas Journal of Biological Diversity, 2009)
Coral reefs play an important physiological and ecological role in coastal ecosystems such as providing natural breakwatersthat protect shorelines and human settlements from waves and storm. Corals killed by tsunami, waves and storms are often degraded into rubble. This rubble is dynamic, easily shifted by currents and storms, which effectively forms ‘‘killing fields’’ forcoral juveniles, hindering coral recovery. In order to rehabilitate coral reefs, artificial substrates are used both for coral transplantation and recruitment. Unfortunately, most artificial substrates are expensive and use land-based material such asconcrete/cement-bases. In order to develop a new low-cost artificial substrate that can replace concrete/cement-base as amedia for coral transplantation, modified coral rubble was tested in a pilot study in Seribu Island, Jakarta. Two different nets (nylon and polyethylene) were used to form rubble into a compact shape, stable and strong substrate. The stability of therubble and the complexity of the surface which is created by the net make this substrate suitable for coral transplantation.Additionally, from an economic perspective the nets are very cheap and locally available. In a number of experiments,modified coral rubble successfully replaced the concrete /cement-base as a media for coral transplantation. The coral transplants were growing over time. With this method, we can try to rehabilitate the degraded coral reef destroyed by tsunami or other factors with material that already is available at the site and with less money. However, this approach requires testing at additional sites and for longer periods, to determine the replicability of the results.Key words: cement base, coral, rubble, transplantation